Design, Synthesis, and Biological Evaluation of Camptothecin Loaded Biotinylated Cellulose Nanowhiskers as Anticancer Agents - Wennas, Osamah N.; Mohammed, Mohammed H.; Al Abood, Raid M.; Abed, Dhulfiqar A (Journal of Contemporary Medical Sciences, 2021)
Objective: Using biotinylated cellulose nanowhiskers (CNWs), we designed and synthesized a Glutathione (GSH) sensitive- Camptothecin (CPT) prodrug for selective CPT delivery (compound 12). Methods: CPT-biotin (compound 9), was synthesized by direct conjugation of CPT to the biotin via GSH sensitive linkage to evaluate the role of CNWs in compound 12. The chemical structures of the synthesized prodrugs were confirmed by FT-IR, 1H NMR, 13C NMR, and ESI-MS, while the nanoparticles were characterized by DLS and TEM. Results: The in-vitro drug release assay demonstrated that only 18.6% of CPT was released from the nano conjugate under GSH stimulation at micromolar level (100 Î¼M), while 83.1% accumulative release rate was achieved under GSH stimulation at millimolar level (10 mM). The in-vitro cytotoxicity assay (MTT assay) demonstrated that compound 9showed higher inhibition ratios on biotin positive cells, MCF-7, and HepG2, and lower cytotoxicity on biotin negative, CHO. Compound 12 showed good activity against MCF-7, HepG2, and much lower cytotoxicity on CHO. Conclusion: This work demonstrates CPT-biotinylated cellulose nanowhiskers for selective chemotherapy and may have the potential to be used for cancer targeting.